2018
DOI: 10.3389/fpsyg.2018.00816
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Symptomatology and Identity Formation in Adolescence: A Cross-Lagged Longitudinal Approach

Abstract: Introduction: Eating disorder symptomatology, comprising both psychological and behavioral aspects of subclinical eating concerns, constitutes a clear precursor of developing eating disorders. It is crucial to investigate its antecedents and correlates to subsequently inform eating disorder prevention programs. The present study focused on identity formation, a core developmental task in adolescence, that has increasingly been linked to eating disorder development. Our main aim was to examine the temporal sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 78 publications
(111 reference statements)
8
44
3
Order By: Relevance
“…The body of literature demonstrating that gaining a sense of control and asserting one's independence from others underlie ED behaviors (e.g., Froreich et al, ) is congruent with the interpersonal boundaries function (e.g., “demonstrating I am separate from other people”) being rated as more salient to ED. Similarly, research suggests that individuals with ED often struggle with forming a cohesive sense of self and experience identity confusion (Verschueren et al, ). An ED diagnosis may provide the person with a sense of identity that distinguishes one from others; thus, reinforcing the autonomy function of the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The body of literature demonstrating that gaining a sense of control and asserting one's independence from others underlie ED behaviors (e.g., Froreich et al, ) is congruent with the interpersonal boundaries function (e.g., “demonstrating I am separate from other people”) being rated as more salient to ED. Similarly, research suggests that individuals with ED often struggle with forming a cohesive sense of self and experience identity confusion (Verschueren et al, ). An ED diagnosis may provide the person with a sense of identity that distinguishes one from others; thus, reinforcing the autonomy function of the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…To examine such a bidirectional relationship, we conducted a 2-year, three-wave longitudinal study with a community sample of adolescents and emerging adults (Verschueren et al, 2018). Cross-lagged analyses indicated that identity confusion appeared to increase one's vulnerability to experience body dissatisfaction and display bulimia symptoms over time relative to the rest of the sample, whereas identity synthesis seemed to protect against the emergence of both.…”
Section: Identity and Ed Symptoms And Pathologymentioning
confidence: 99%
“…relationships; vocation; ideology) [ 50 ]. Furthermore, burgeoning research has identified the important interplay between ED aetiology /treatment response and ongoing developmental context, with concurrent identity development identified as particularly relevant [ 9 , 10 , 37 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%